Wireless communication circuits and systems - Sun, Yichuang (London, United Kingdom Institution of Engineering and Technology, 2004)
This book is concerned with integrated circuits and systems for wireless and mobile communications. Circuit techniques and implementation of reconfigurable low-voltage and low-power single-chip CMOS transceivers for multiband and multi mode universal wireless communications are the focus of the book. Applications encompass both long-range mobile cellular communications (GSM and UMTS) and short-range wireless LANs (IEEE802.11 and Bluetooth). Recent advances in research into transceiver architecture, RF frontend, analogue baseband, RF CAD and automatic testing are reported. The book, containing ten chapters, covers topics including receiver architectures, reconfigurable and programmable analogue base band arrays, design and on-chip tuning of active IC filters including polyphase filters, receiver front-end modules (LNA, VCO, mixer) and chips, transmit power amplifiers, parasitic-aware RF design and optimisation, and on-chip testing of communication ICs. The book can be used as a text or reference book for a broad range of readers from both academia and industry.
Electronic reproduction.
Keywords: Wireless communication systems; Electronic circuits; Electronic books